2002
DOI: 10.1209/epl/i2002-00392-7
|View full text |Cite
|
Sign up to set email alerts
|

Specific heat and disorder in the mixed state of non-magnetic borocarbides

Abstract: The temperature and magnetic-field dependence of the specific heat cp(T, H) in the superconducting (sc) mixed state as well as the upper critical field Hc2(T ) have been measured for polycrystalline YxLu1−xNi2B2C and Y(Ni1−yPty)2B2C samples. The linear-in-T electronic specific-heat contribution γ(H) • T exhibits significant deviations from the usual linear-in-H law resulting in a disorder-dependent negative curvature of γ(H). The Hc2(T ) data point to the quasi-clean limit for (Y, Lu)-substitutions and to a tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…On the other hand, a recent study of magnetic field orientation dependence of the specific heat has indicated line nodes, where the lines are parallel to the k z axis and pass through the k x and k y axes in the Brillouin zone . We note that these point-node and line-node Nohara et al 1999Nohara et al , 2000; see also Lipp et al 2002). This work focussed on the magnetic field dependence of the specific heat g at T << T c , where the peaks for both of these materials (Mizuno et al 1999(Mizuno et al , 2000.…”
Section: Borocarbidesmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, a recent study of magnetic field orientation dependence of the specific heat has indicated line nodes, where the lines are parallel to the k z axis and pass through the k x and k y axes in the Brillouin zone . We note that these point-node and line-node Nohara et al 1999Nohara et al , 2000; see also Lipp et al 2002). This work focussed on the magnetic field dependence of the specific heat g at T << T c , where the peaks for both of these materials (Mizuno et al 1999(Mizuno et al , 2000.…”
Section: Borocarbidesmentioning
confidence: 99%
“…This seems to support the conjecture.] There is some data in poor agreement with this model (Miller et al 2000, 2001, Schmiedeshoff et al 2001, Lipp et al 2002, but for these the smaller power-law exponents might possibly be due to having multiple conduction bands with different gap magnitudes (Nakai et al 2002, Boaknin et al 2002. (See also Amin et al 2000, Dahm et al 2002b, Kusunose et al 2002.)…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…For example, variation of electronic specific heat C el as a function of temperature in the superconducting state in pure YNi 2 B 2 C follows a power law, C el ∼ (T/T c ) 3 (anisotropic energy gap) whereas it exhibits an exponential T-dependence in the material YNi 1.8 Pt 0.2 B 2 C (isotropic energy gap) [5,6]. T c is not affected significantly with the introduction of Pt (T c ∼ 12.2 K in YNi 1.8 Pt 0.2 B 2 C; T c = 15.5 K in YNi 2 B 2 C); however, variation of the upper critical field H c2 as a function of x clearly shows that the material passes from the clean limit to the dirty limit with the increase of x [7].…”
Section: Introductionmentioning
confidence: 95%